Skin microvasculature in different types of diabetic foot ulcer : a comparative study - Hazulin Mohd Radzuan (Kulliyyah of Medicine, International Islamic University Malaysia, 2013)
Morphological changes affecting endothelial cells of skin microvasculature in diabetic foot ulcer (DFU) may indicate microcirculatory dysfunction and subsequently leads to poor healing of ulcer. In this study, I have analysed 42 subjects, involving 10 controls, 16 patients with neuropathic DFU and 16 patients with neuroischaemic DFU. The specimens were taken by using skin punch biopsy and routinely processed for light microscopy. I have calculated and measured the mean endothelial cell count (ECC), endothelial cell thickness (ECT) and luminal area:outer vessel area ratio in percentage (LA) from 3 selected arterioles and capillaries in each slide of every patient. There were significant decrement in ECC and LA among the diseased group as compared to the controls, F (2, 39) = 9.20, p = 0.01 and F (2, 39) = 17.54, p < 0.05. While the ECT of the diseased group were significantly higher than the controls, F (2, 39) = 66.11, p < 0.05. The Tukey post-hoc comparisons indicate that the ECC between neuropathic and neuroischemic group was insignificant, but the ECT and LA revealed significant differences as p < 0.05. In conclusion, the decrement of ECC and LA, and the increment of ECT among different types of DFU patients show endothelial cells adaptation towards diabetic state, thus affecting the patency of skin microvasculature and may signify different prognosis in different types of DFU.